Early adopters of ORCID functionality enabling recognition of peer review: Two brief case studies. Issue 1 (8th January 2016) - Hanson, Brooks; Lawrence, Rebecca; Meadows, Alice; Paglione, Laura
Abstract : Key points Publishers increasingly acknowledge the need for better recognition of peer review activities and are experimenting with ways to achieve this. A recent community working group recommended a set of data exchange standards to support this recognition, and these have now been implemented by the Open Researcher and Contributor ID. The American Geophysical Union and F1000 are the first adopters of this new functionality.